Revealing masks : exotic influences and ritualized performance in modernist music theater - Sheppard, William Anthony, 1969- (California studies in 20th-century music, 2001)
W. Anthony Sheppard considers a wide-ranging constellation of important musical works in this exploration of ritualized performance in 20th-century music. 'Revealing Masks' uncovers the range of political, didactic, and aesthetic intents that inspired the creators of modernist music theatre.